Gender differences in truancy: A case study at Alma Secondary School, Pulau Pinang / Mohd Khairussani Elias and Nur E’zzati Ahmad Kamal - Elias, Mohd Khairussani; Ahmad Kamal, Nur E’zzati (Faculty of Administrative Science and Policy Studies, 2013)
Truancy among students is a major disciplinary problem. In this study, researchers are focuses on the gender differences in truancy: a case study at Alma Secondary School, Pulau Pinang. The objective are to find out the significant differences between gender and the individual factor with students’ truancy, to identify the significant differences between gender and the family factor with students’ truancy, to identify the significant differences between gender and the social factor with students, truancy, to identify the significant differences between gender and the school environment factor with students’ truancy and to find out the most factors influencing student’s truancy. There were 915 students from Form One to Form Five and only 269 students were selected based on Morgan sampling technique and convenience sampling. This descriptive analysis used questionnaires as a research instrument that consist of five sections namely respondent’s profile (section A) and factors that contribute to students’ truancy which are individual (section B), family (section C), social (section D) and school environment (section E). The data obtained was analyzed using “Statistically Packages for the Social Science” (SPSS) version 20 and was presented in descriptive analysis, reliability analysis, testing for normality and chi-square analysis. The researcher’s findings showed that there are no significant differences between gender and the factors that influence student’s truancy. Other than that, the findings also find out the most influencing factors of student truancy which are family factor. Based on findings, the researchers also stated recommendations to overcome student’s truancy in Alma Secondary School.